Solvent and Autocatalytic Effects on the Stabilisation of the σ‐Complex during Electrophilic Aromatic Chlorination. Issue 27 (25th April 2018) - Van Lommel, Ruben; Moors, Samuel L. C.; De Proft, Frank
Abstract: The solvent and autocatalytic effects of the electrophilic aromatic chlorination of benzene are studied using a combined approach of static calculations and ab initio metadynamics simulations. Different possible reaction pathways are investigated and the influence of the solvents (CCl4, acetonitrile and acetic acid) is thoroughly assessed. Our results show that the stability and lifetime of a charged σ‐complex is increased by electrostatic stabilisation effects of the environment, which can originate from catalytic HCl, solvating effects of polar solvents (acetonitrile), or specific hydrogen bonding interactions with the solvent (acetic acid). Metadynamics simulations reveal a new chlorine addition mechanism explaining the autocatalytic effects of the reaction. The strength of combining static calculations and metadynamics simulations is highlighted, which provide complementary insight into chemical reactions in solvent. Abstract : Although the electrophilic aromatic substitutions are a well‐known class of reactions, the mechanism is still a matter of debate. In this work, the solvent and autocatalytic effects of the aromatic chlorination were studied by using a combined approach of static calculations and metadynamics simulations.